Augmentation of human monocyte opsonin-independent phagocytosis by fragments of human plasma fibronectin. - Czop, J K (1981)
Human plasma fibronectin isolated by gelatin-affinity chromatography increases in a dose-dependent fashion the number of human monocytes that ingest particulate activators of the human alternative complement pathway in a fully synthetic medium. The fibronectin effect is selective for these particulate activators, does not extend to particles whose ingestion is dependent upon opsonization with IgG, and is not observed with pretreatment of the monocytes. Affinity chromatography with monoclonal antibody to plasma fibronectin of 440,000 daltons reveals that only 12-53% of the protein in a phagocytically active gelatin-affinity-purified fibronectin preparations is bound to the antibody. The protein eluted after affinity chromatography with monoclonal antibody of active preparations, which represented 10-43% of the protein applied, exhibits a 2- to 10-fold increment of activity per microgram of protein above the starting gelatin-affinity-purified material. Thus, the activity that augments the percent of human monocytes ingesting particulate activators of the alternative pathway is antigenically defined as plasma fibronectin. Preparations containing only intact 440,000-dalton fibronectin are also bound to and eluted from the monoclonal antibody, but they fail to augment phagocytosis. When inactive 440,000-dalton plasma fibronectin is subjected to limited trypsin cleavage, phagocytosis-enhancing activity develops that is bound to and elutes from the affinity column prepared with monoclonal antibody, thereby indicating that the enhancing activity of plasma fibronectin resides in cleavage fragments.